Computational and Experimental Studies of Acoustic Waves - Reyhanoglu, Mahmut (IntechOpen, 2018)
This book presents recent studies of acoustic wave propagation through different media including the atmosphere, Earth's subsurface, complex dusty plasmas, porous materials, and flexible structures. Mathematical models of the underlying physical phenomena are introduced and studied in detail. With its seven chapters, the book brings together important contributions from renowned international researchers to provide an excellent survey of recent computational and experimental studies of acoustic waves. The first section consists of four chapters that focus on computational studies, while the next section is composed of three chapters that center on experimental studies.